Visual Assessment of 18F-FDG Uptake on PET to Predict Survival Benefit to PD-1 Blockade in Non–Small Cell Lung Cancer. (February 2022) - Hashimoto, Kosuke; Kaira, Kyoichi; Yamaguchi, Ou; Shiono, Ayako; Mouri, Atsuto; Miura, Yu; Kobayashi, Kunihiko; Imai, Hisao; Matsusaka, Yohji; Kuji, Ichiei; Kagamu, Hiroshi
Abstract : Supplemental digital content is available in the text. Abstract : Background: Programmed death 1 (PD-1) blockade is a standard treatment for patients with metastatic non–small cell lung cancer (NSCLC). Approximately 20% patients receiving PD-1 blockade monotherapy can survive for more than 5 years. However, there are limited data on the optimal biomarkers for predicting long-term outcomes. Therefore, this study aimed to evaluate the prognostic significance of 18 F-FDG uptake in patients with NSCLC responding to PD-1 blockade. Patients and Methods: Thirty-eight patients with advanced NSCLC who underwent 18 F-FDG PET after confirmation of clinical response to PD-1 blockade monotherapy were retrospectively included in this study. Visual assessment using a 5-point scale score according to 18 F-FDG uptake was performed, and the 18 F-FDG uptake cutoff score for prolonged response to PD-1 blockade was defined as 3 (low score: 1, 2, or 3 and high score: 4 or 5). Results: A significantly greater number of patients with low scores had a performance status of 0 or 1 than patients with high scores. Among the 38 patients, 20 (53%) had a low score and 18 (47%) had a high score. Progression-free survival and overall survival were significantly longer in patients with low scores than in patients with high scores. Low 18 F-FDG uptake was an independent prognostic factor for predicting favorable progression-free survival and overall survival, as confirmed by multivariate analysis. Conclusions: Tumors with lower 18 F-FDG uptake on PET than normal hepatic lesions exhibit the possibility of prolonged response to PD-1 blockade. Visual assessment on PET is easy for every clinician and is understandable to confirm aggressive tumor activity.